Effect of progression-free interval (PFI) following penultimate platinum-based regimen on the efficacy of rucaparib maintenance treatment in patients with platinum-sensitive, recurrent ovarian carcinoma: an analysis from the phase 3 study ARIEL3. (1st November 2019) - Clamp, AR; Oza, AM; Lorusso, D; Aghajanian, C; Oaknin, A; Dean, A; Colombo, N; Weberpals, JI; Scambia, G; Leary, A; Holloway, RW; Amenedo Gancedo, M; et al.
Abstract : Introduction/Background: In ARIEL3, rucaparib maintenance treatment significantly improved progression-free survival (PFS) vs placebo in all patient populations, regardless of biomarker status (Coleman et al. Lancet . 2017;390:1949–61). This subgroup analysis examined the effect of the stratification factor PFI following penultimate platinum-based chemotherapy (also a prognostic factor in ovarian cancer) on primary and secondary endpoints of investigator-assessed and blinded independent central review (BICR)-assessed PFS in ARIEL3. Methodology: Patients were randomised 2:1 to oral rucaparib (600 mg BID) or placebo. Analysis was based on the randomisation stratification factor of PFI following penultimate platinum-based regimen: 6–12 months or >12 months. PFS was assessed in 3 predefined cohorts: BRCA mutant; BRCA mutant + BRCA wild type/high loss of heterozygosity (LOH high); and intent-to-treat (ITT) population. Safety was assessed in all patients who received ≥1 dose of rucaparib. Results: Visit cutoff dates for efficacy and safety were 15 April 2017 and 31 December 2017, respectively. For all predefined cohorts, investigator and BICR assessments showed a significant PFS improvement with rucaparib vs placebo in both PFI subgroups (figure 1 ). As expected, patients receiving placebo with a PFI 6–12 months had a shorter median PFS than those with a PFI >12 months. The treatment by PFI subgroup interaction was not significant, indicating that the treatment benefit was similar in both PFI subgroups. Safety data in the PFI subgroups were consistent with the overall study population, as previously reported. Conclusion: In ARIEL3, rucaparib maintenance treatment significantly improved PFS vs placebo in all cohorts, irrespective of PFI subgroup. The magnitude of treatment effect was similar for both PFI subgroups. Disclosure: ARC: AstraZeneca, Roche, Clovis AMO: Clovis, Amgen, Immunovaccine, Verastem, AstraZeneca, WebRx DL: Clovis, AstraZeneca, ImmunoGen, Merck, PharmaMar, Roche, Takeda, Tesaro CA: Clovis, Mateon, Bayer, Cerulean, Tesaro, VentiRx AO: Clovis, AstraZeneca, ImmunoGen, Genmab/Seattle Genetics, PharmaMar, Roche, Tesaro AD: Precision Oncology Australia, Shire Pharmaceuticals, Specialised Therapeutics Australia NC: Clovis, Advaxis, AstraZeneca, BIOCAD, MSD, Pfizer, PharmaMar, Roche, Takeda, Tesaro JIW: AbbVie, AstraZeneca GS: Clovis, AstraZeneca, PharmaMar, Roche, Tesaro AL: Clovis, Pfizer, PharmaMar, GamaMabs, Merus, AstraZeneca RWH: Clovis, AstraZeneca, Tesaro MAG: Clovis, AstraZeneca, PharmaMar, Roche PCF: Clovis, AstraZeneca JCG: AstraZeneca, BMS, Janssen, Ipsen, MSD, Astellas DMO'M: Clovis, AstraZeneca, Gynecologic Oncology Group, Janssen, Myriad, Tesaro, Amgen, ImmunoGen, AbbVie, Ambry, Health Analytics, Agenus, Ajinomoto, Array BioPharma, BMS, ERGOMED Clinical Research, Exelixis, Genentech, GSK, INC Research, inVentiv Health Clinical, Ludwig Institute for Cancer Research, Novartis, PRA International, Regeneron, Serono, Stemcentrx, TRACON DKA: Morphotek, Clovis, Advaxis, AstraZeneca, Pfizer, Syndax, Tesaro SB: Clovis, AstraZeneca, ImmunoGen, GamaMabs, Merck Serono, PharmaMar, Roche, Seattle Genetics, Tesaro JG-D: AstraZeneca, Clovis, Genentech/Roche, Janssen EMS: nothing to disclose TC, LM, SG: Clovis RLC: Clovis, AbbVie, AstraZeneca, Esperance, Janssen, Merck, Millennium, OncoMed, Roche/Genentech, Bayer, GamaMabs, Genmab, Gradalis, Pfizer, Tesaro JAL: Clovis, AstraZeneca, Pfizer, Artios Pharma, Cristal Therapeutics, MSD, Regeneron, Roche, Seattle Genetics, Tesaro.